Language intervention for late talkers: the experiences of speech-language pathologists in Malaysia = (Intervensi bahasa untuk kanak-kanak lambat bercakap: pengalaman terapis pertuturan-bahasa di Malaysia) - Tukiran, Nur Hanisah; Mohamed Zain, Nor Azrita; Ali Hanafiah, Nurlin (UKM Press, 2023)
A few studies have investigated the practise patterns of Malaysian speech-language pathologists (SLPs) when working with children with speech and language problems whose language intervention is necessary. However, these studies did not provide in-depth information about the SLPs' experiences as the studies were conducted quantitatively. Moreover, none of the studies focus on late-talkers (LTs), in which intervention for them can vary along a continuum from a wait/watch-and-see approach to direct intervention. Thus, this study aimed to explore SLPs’ experiences in managing LTs in Malaysia. Twelve SLPs participated in individual, semi-structured phone interviews. They were asked about their experiences in managing LTs. The interviews were recorded, transcribed, and a content analysis was performed. Two themes were identified; a) practises of SLPs and b) challenges faced by SLPs in managing LT cases. The practises of SLPs included conducting assessments, developing intervention plans, providing intervention, sharing information, giving homework, providing support, and managing appointments. The challenges faced were related to parents, other individuals close to LTs, LTs themselves, and resources. Although the SLPs’ practises aligned with the international standard of speech-language pathology service delivery, there is room for improvement, especially in collaborating with parents, as one-to-one direct interventions for LTs might not be suitable due to the challenges related to resources. In addition, a few suggestions related to centred-based care and trusted social media pages can be provided to parents to assist them outside therapy sessions besides initiating the development of awareness programs and information resources for parents and other caregivers.